(untitled) (Journal of Science and Technology, 2016)
This paper reviews the main determinants of productivity and quality of forage from browse species and highlights the usefulness of browse plants as fodder sources. The effect of secondary plant metabolites on forage quality and the consequential effects on browse acceptability and intake are presented. Condensed tannin (CT) is emphasised due to its nutritional advantage if it occurred at an acceptable level (< 50 gCT/ kg DM). The practical implication of this limit has been questioned and it is speculated that it may vary with plant species as the function of CT depends on its structure and level of polymerisation. Gaps in our knowledge of browse plants are identified and areas requiring further research are indicated.